Genomic data from White-flippered penguin ( Eudyptula minor albosignata ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The White-flippered penguin is a small penguin closely related to the New Zealand little blue penguin. It is occasionally considered a unique species or sometimes a subspecies of the New Zealand little blue penguin, however genetic research indicates that the two taxa are probably incipient. The reason it is occasionally considered a separate species or subspecies is because it has white markings on its flippers. Most taxonomists consider it to be a colour morph of the New Zealand little blue penguin. It nests in headlands, caves, rock jumbles and in the sheltered areas at the bases of bays, only on Banks Peninsula and Motunau Island near Christchurch, New Zealand. The white-flippered penguin is a Taonga, or treasured possession in Mori culture. The International Union for Conservation of Nature (IUCN) considers all Eudyptula penguins as least concern. We sequenced the genome of an adult White-flippered penguin from Christchurch Antarctic Centre, originally from Banks Peninsula, Canterbury, New Zealand South ...